ANALISIS SEKTOR UNGGULAN MENGGUNAKAN DATA PDRB (Studi Kasus BPS Kabupaten Kendal Tahun 2006-2010) - Rosita Wahyuningtyas; Agus Rusgiyono; Yuciana Wilandari (Jurnal Gaussian, 2013)
Gross Domestic Regional Product (GDRP) is total numbers of added values who’s producting by effort unit in that domestic area’s. GDRP can be classified in two form, that is GRDP at Current Market Prices and GRDP at Constant Prices. GRDP at Current Market Prices is calculating with two approaches, those are approach production and approach income. GRDP at Constant Prices can be calculated using two methods, revaluation and deflation. By using GDRP data, then it can be known which sector is  prominent sector in that region. Some methods who using GDRP data as decisive prominent sector is method of Typology Klassen, LQ, MRP, Overlay and Shift Share. These methods classifying the economic sectors into four groups, they are prominent sector, growing sector, potential sector and under developed sector, based on large of contribution and rate of growth. By taking the study area Kendal Regency and reference area is province Central of Java, then by used that methods can be known which sector be prominent sector in Kendal Regency. Based on the result from analysis methods, they are same result about prominent sector: agriculture sector and mining and quarrying sector